Nutritional management in children with disease-related malnutrition : what’s the guideline? - I Gusti Lanang Sidiartha (World Nutrition Journal, 2022)
Background: Disease-related malnutrition (DRM) is one of the most common problems in pediatric patients. Both cancer and congenital heart diseases (CHD) are commonly associated with DRM. Altered nutrition utilization, reduced intake, malabsorption, and hypermetabolism are the main pathophysiology in DRM. Method: A systematic literature searching was performed through Pubmed and Google Scholar websites. Thirty-six articles were included into the study. Results: Malnutrition screening should be performed as soon as possible since early feeding can benefit the patients. One of the most commonly used tools is Screening Tool for Risk on Nutritional Status and Growth (STRONGkids), which was proven to be valid, reproducible, and applicable in pediatric patients with malnutrition. Following screening and assessment, nutrition support can ensue, preferably in the form of enteral nutrition, unless contraindicated. Nutrient-dense formula, also known as protein and energy-enriched formula, aims to aid infants to reach nutrition target rapidly and stimulate anabolism. This formula has been studied in various population, mostly infants with CHD and studies showed favorable outcomes with its administration, namely faster improvement, reduced diuretics use and oxygen supplementation, decreased length of hospital stay, and less antibiotic use. Nutrient-dense formula is also safe and well-tolerated. Conclusion: Proper screening and management should be performed with multidisciplinary approach to achieve the best outcome in children with DRM.